PENGARUH DEBT TO EQUITY RATIO DAN RETURN ON ASSET TERHADAP HARGA SAHAM PT KRAKATAU STEEL TBK PERIODE 2014-2023 - Meytha Billa Pree Arsantha; Nurwita Nurwita (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research method uses quantitative descriptive. The data used is secondary data. The population of this research is the entire financial report of PT Krakatau Steel Tbk and the sample used is the balance sheet and profit and loss financial report of PT Krakatau Steel Tbk for the period 2014-2023. Based on the calculation results of the Determination Coefficient Test, it is known that the R^2 value is 20.3%, meaning that it shows that around 70.97% of the Stock Price variable is explained by other variables, while the Debt to Equity Ratio and Return on Assets only influence 20.3 %. The results of this research show that partially the Debt to Equity Ratio variable does not have a significant effect on share prices with a significance of 1,302 > 0.05, while partially Retun on Assets does not have a significant influence on share prices with a significant 0.311 > 0.05. Simultaneously the Debt to Equity Ratio and Return on Assets do not have a significant effect on share prices where the F value is 0.893 with a significant value of 0.452 > 0.05.